Perubahan Sosial dalam Falsafah diri Masyarakat Kepulauan Banda - Murwani, Prapti; Watloly, Aholiab; Saija, Dominggus E.B.; Wijayai, Firdhan A. (Jurnal Noken: Ilmu-Ilmu Sosial, 2025)
This study aims to explore and analyse social changes in the self-philosophy of the Banda Islands community, known as the Banda people. This research identifies that their self-philosophy has always been influenced by dynamic historical changes, with the phases of construction, deconstruction, and reconstruction as the main processes in their social journey. The problem faced is how to examine the essence of the Banda people, which has been lost in the darkness of history, and restore healthy personality values to create a democratic and prosperous society. The method used is historical philosophical analysis to understand the social and cultural changes of the Banda people. The results of the study show that in order to revive the essence of identity and strengthen the intellectual and spiritual power of the community, it is necessary to reconstruct a philosophy of identity that is in line with diversity and innovation. In conclusion, reconciliation and reconstruction of the Banda people's philosophy of identity is very important to achieve shared prosperity, which requires strong support from the central and regional governments as well as various related parties.